2022
DOI: 10.3390/ijms23116284
|View full text |Cite
|
Sign up to set email alerts
|

Bos taurus and Cervus elaphus as Non-Seasonal/Seasonal Models for the Role of Melatonin Receptors in the Spermatozoon

Abstract: Melatonin is crucial in reproduction due its antioxidant, hormonal, and paracrine action. Melatonin membrane receptors (MT1/MT2) have been confirmed on spermatozoa from several species, but functionality studies are scarce. To clarify their role in ruminants as reproductive models, bull (Bos taurus, non-seasonal) and red deer (Cervus elaphus, highly seasonal) spermatozoa were analyzed after 4 h of incubation (38 °C, capacitating media) in 10 nM melatonin, MT1/MT2 agonists (phenylmelatonin and 8M-PDOT), and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…It is able to balance the mitochondrial membrane potential (Jauhari A, 2020 ) and is classified as a mitochondria-targeting antioxidant (Tan DX, 2020 ). Research shows that MT1 was found to have a variable distribution on the sperm head, depending on the spermatozoa and the individual male, whereas MT2 seems to be more restricted to the post-acrosomal and neck regions (Fernández-Alegre E, 2022 ), where are enriched with mitochondria. To address this point in more depth, in addition to exploring the mitochondrial morphology of HS and MT sperm, the link between them can be determined by comparing the proportion of different types of malformed sperm under different conditions, whether the typical heat-stressed malformed sperm is head, neck or tail malformed and which type of sperm is significantly reduced following melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is able to balance the mitochondrial membrane potential (Jauhari A, 2020 ) and is classified as a mitochondria-targeting antioxidant (Tan DX, 2020 ). Research shows that MT1 was found to have a variable distribution on the sperm head, depending on the spermatozoa and the individual male, whereas MT2 seems to be more restricted to the post-acrosomal and neck regions (Fernández-Alegre E, 2022 ), where are enriched with mitochondria. To address this point in more depth, in addition to exploring the mitochondrial morphology of HS and MT sperm, the link between them can be determined by comparing the proportion of different types of malformed sperm under different conditions, whether the typical heat-stressed malformed sperm is head, neck or tail malformed and which type of sperm is significantly reduced following melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%